Modern Feminism according to Jeannette Winterson - Tichá, Veronika (Univerzita Pardubice, 2008)
Jeanette Winterson, a modern contemporary British feminist writer of the 20th century, deals with lesbian themes, gender and sexuality in her work. The main focus of this work is to investigate Winterson´s historical place in the feminist’s movement and to analyze her first famous book Oranges Are Not the Only Fruit from the feminist and lesbian point of view. This work introduces the theory and history of feminism and focuses on Winterson´s attitude towards feminism, gender and sexuality and on her writing technique. Further, it provides a complete analysis of Oranges with reference to its feminist and lesbian features.
Moderní feminismus podle Jeannette Winterson
Keywords: feminismus; patriarchát; lesbismus; pomeranč; Jeanette Winterson; feminism; patriarchy; lesbianism; orange; Gender